Case Report: A rarely observed anomaly of the common bile duct—common bile duct duplication - Bilgi Kirmaci, Mehlika; Balli, Emre; Dayanç, Murat; Yilmaz, Sezgin (Frontiers in Medicine, 2025)
Extrahepatic biliary anomalies are rarely diagnosed. These anomalies are usually detected incidentally after investigating clinical findings in patients such as obstructive jaundice, pancreatitis, or biliary tract malignancies. In our study, we describe common bile duct duplication in a patient scheduled for palliative hepaticojejunostomy due to unresectable pancreatic cancer. We are presenting a case with type I common bile duct anomaly.